Determinant of Entrepreneurial Intention - Annio Indah Lestari Nasution; Aulia Indriani Suryono (Management Department Universitas Islam Negeri Sumatera Utara, 2021)
The high percentage of educated unemployment rate in North Sumatra who graduated from universities and diplomas is caused by the low supply of employment, high-income expectations, and skills that do not fit into the needs of employment providers. Therefore, students and undergraduates should be able to overcome this problem by becoming entrepreneurs and even creating employment. In other words, students should have an intention in entrepreneurship or an interest in starting a business. This study aimed to determine the influence of several contexts that influence entrepreneurial intentions. This research is quantitative. The number of samples in this study was 68 people from students majoring in Islamic Economics, UIN North Sumatra. Data was collected by distributing questionnaires and using multiple linear regression analysis with SPSS. This study's results indicate a positive but insignificant influence between the family context variables on entrepreneurial intentions and a positive and significant influence between the educational context variables on entrepreneurial intentions. The constraints variable in starting a business does not significantly affect entrepreneurial intentions. Simultaneously, the context of the family, education, and the barriers to starting a business have significantly affected entrepreneurial intentions, as indicated by the significant value of F <α (0.001 <0.05). Keywords: Education, entrepreneurial intention, family, obstacles of starting business